Global meets digital : global strategy for digital businesses : digital strategy for global businesses - Jain, Vinod Kumar (Productivity Press, 2023)
The world today is at the intersection of two megatrends - Globalization and Digitalization - a business revolution unfolding in real time. Global Meets Digital captures the many nuances of this revolution succinctly, including its impact on our lives and business. An immediate implication of this revolution is that the economic principles that underpinned business and strategy for hundreds of years, such as diminishing returns to scale and resource scarcity, are no longer valid for a large and growing number of products and services. The book will challenge you to think differently not just about digital products, but also about physical products. In the global-digital world, products are of three kinds--physical, digital, and smart machines (products that are both physical and digital, and connected to the internet)--a distinction missed by most books on strategy and global business. The economics of each kind of products is distinct from that of the others, which has strategic implications for all kinds of businesses -implications such as how to compete and how to create and capture value. With several mini case studies and over 300 company examples, the book covers themes and cutting-edge issues like the paradox of globalization, digital disruption, disruptive business models, exponential technologies, Internet of Things, competition in digital markets, winner-take-all market dynamics, Industry 4.0, how to innovate, strategizing for the New Normal, and value creation and value capture in both B2C and B2B contexts. The book derives its underpinnings from the practice of global and digital business, while theory remains in the background. Intended specifically for an executive/professional audience, Global Meets Digital should also be of value to business students and professors learning to dip their toes into a digital world. Vinod Jain is an expert in global and digital strategy, award-winning professor, Fulbright Scholar, and author of an MBA textbook, Global Strategy. He taught at the Rutgers Business School, Newark and New Brunswick, and the Robert H. Smith School of Business, University of Maryland, College Park. At Maryland, he was also the Founding Director of the federally funded Center for International Business Education and Research and Academic Director of Smith School's Executive MBA program in China. Since leaving Maryland, he has taught in China, Denmark, Finland, Poland, and India as a visiting or term professor. His opinion pieces have appeared in The Washington Post, The Baltimore Sun, Mensa Bulletin, and Economic Times and Mint (India's #1 and #2 business dailies), among other media. In the past, he worked as a middle- and senior-level executive with American and British multinationals. Vinod has a PhD in Strategy and International Business from the University of Maryland, College Park, MS in Management from UCLA, and MS and BS (Hons) in Statistics from the Indian Statistical Institute, Calcutta.